THE EFFECT OF AGENT COMPETENCY, PERFORMANCE AND COMMUNICATION IN INCREASING CUSTOMER TRUST IN PT. ASURANSI UMUM BUMI PUTERA MUDA 1967 MEDAN BRANCH - Ujung, Siti Khoiriyah Karina; Lubis , Fauzi Arif; Nasution, Yenni Samri Juliati (International Journal of Cultural and Social Science, 2025)
Customer trust is a major factor in the insurance industry, especially in maintaining customer loyalty and increasing business growth. The purpose of this study was to study the influence of agent performance and communication with PT Asuransi Umum Bumi Putera Muda 1967 Medan Branch Office on the level of customer trust. This study was conducted with a quantitative approach through the use of the structural equation method (PLS-SEM). Data were collected from 89 customers who were currently active in the company. The results showed that agent performance did not have a significant effect, but agent ability and communication had a significant positive impact on customer confidence. The findings of this study revealed that increasing competence can strengthen consumer trust and agent communication, while increasing agent performance does not directly increase customer trust. Therefore, companies need to emphasize agent competency training and strengthen effective communication with customers in order to improve long-term relationships.